2009
DOI: 10.3386/w15555
|View full text |Cite
|
Sign up to set email alerts
|

Testing Theories of Scarcity Pricing in the Airline Industry

Abstract: This paper investigates why passengers pay substantially different fares for travel on the same airline between the same two airports. We investigate questions that are fundamentally different from those in the existing literature on airline price dispersion. We use a unique new dataset to test between two broad classes of theories regarding airline pricing. The first group of theories, as advanced by Dana (1999b) and Gale and Holmes (1993), postulates that airlines practice scarcity based pricing and predicts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 24 publications
2
37
1
Order By: Relevance
“…First, the evidence reported in Figure 3 suggests that YM techniques designed by airlines to manage capacity constitute an important factor driving fares' dispersion. Interestingly, despite the methodological similarity, Puller et al (2009) reach an opposite conclusion in their study of U.S. airline markets. 12 Second, it introduces the need to combine capacity concerns with at least two other aspects of YM: 1) the fares' temporal profile, i.e., the possibility that fares may change regardless of the flight's occupancy rate and 2) the discretional intervention of an yield manager to tackle unexpected contingencies.…”
Section: The Fare-occupancy Rate Schedulementioning
confidence: 83%
See 4 more Smart Citations
“…First, the evidence reported in Figure 3 suggests that YM techniques designed by airlines to manage capacity constitute an important factor driving fares' dispersion. Interestingly, despite the methodological similarity, Puller et al (2009) reach an opposite conclusion in their study of U.S. airline markets. 12 Second, it introduces the need to combine capacity concerns with at least two other aspects of YM: 1) the fares' temporal profile, i.e., the possibility that fares may change regardless of the flight's occupancy rate and 2) the discretional intervention of an yield manager to tackle unexpected contingencies.…”
Section: The Fare-occupancy Rate Schedulementioning
confidence: 83%
“…However, a more complex fares' dynamics consistent with a combined use of both CS and APD is also found over the entire booking period we take into consideration: in the two months preceding departure the intertemporal profile of a standard flight's fares often appears to be U-shaped, especially in flights that fill up well in advance of departure. While the existing 4 literature has already identified that fares generally tend to increase as the departure date nears (Bilotkach et al, 2010;Puller et al, 2009), to our knowledge no previous contribution has illustrated a U-shaped temporal profile of fares.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations